Memories, identity and homeliness: the social construction of mealtimes in residential care homes in South Wales - Joy Merrell (Ageing and Society, 2013)
Mealtimes in residential care homes are social occasions which provide structure to the day and opportunities for conversation and companionship. There is a paucity of research exploring care home residents’ mealtime experiences in the United Kingdom. Particular findings from a qualitative study which investigated factors influencing nutritional care provided to residents in two different types of residential care settings in South Wales, UK are reported. Methods of data collection included focus group interviews with staff (n=15), individual interviews with managers (n=4) and residents (n=16) of the care homes and their informal carers (n=10), observation of food preparation and meal times and documentary review. Data were analysed using thematic analysis. We report on how the residents’ experiences and understandings of mealtimes were influenced by various environmental factors, such as the home’s geographical location, physical lay-out and ambience. In addition, how the shared meaning of mealtimes for residents, informal carers and staff was constructed from each group’s socio-cultural background, family experiences and memories and was integral to residents’ sense of normality, community and identity.